LncRNA H19 interacts with S-adenosylhomocysteine hydrolase to regulate LINE-1 Methylation in human lung-derived cells exposed to Benzo[a]pyrene. (September 2018) - Fu, Ye; Wang, Wubin; Li, Xuejing; Liu, Yanli; Niu, Yingying; Zhang, Bin; Nie, Jisheng; Pan, Baolong; Wang, Ruisheng; Yang, Jin
Abstract: Benzo [ a ]pyrene (BaP) have been demonstrated to induce lung cancer risk in humans and many different animal models, with aberrant gene methylation as one of the epigenetic errors; however, the molecular mechanisms remain unclear. Here, we used three types of human lung-derived cells with BaP exposure as a model and attempted to investigate the long non-coding RNA (lncRNA) H19 /S-adenosylhomocysteine hydrolase (SAHH) pathway that regulates gene methylation in vitro exposure to BaP. Results showed that compared to the controls, BaP-treated cells H19 expressions were increased in a dose- and time-dependent manner, whereas SAHH protein expressions were decreased. Indeed, H19 binds to and attenuates SAHH expressions and activity, and this interaction will be enhanced by BaP. However, suppression of H19 exaggerates SAHH protein expression and activity exposed to BaP. Although BaP-treated cells H19 single knockdown expectedly increased long interspersed nuclear elements-1 ( LINE-1 ) methylation and inhibited benzo [ a ]pyrene-7, 8-dihydrodiol-9, 10-epoxide (BPDE) -DNA adducts formation with altering SAHH protein expressions and activity, the double knockdown restored methylation to the control level and exacerbated BPDE-DNA adducts formation. Overall, our results uncover a H19 /SAHH circuit involving gene-methylation alterations by carcinogen BaP. Highlights: Carcinogen BaP was studied on three types of human lung-derived cells in vitro. BaP treatment enhances the interaction of H19 and SAHH. Suppression of H19 exaggerates SAHH protein expression and activity exposed to BaP. H19 /SAHH regulates LINE-1 methylation exposed to BaP.